Analgesic efficacy and risk of low-to-medium dose intrathecal morphine in patients undergoing cardiac surgery: An updated meta-analysis - Chen, I-Wen; Sun, Cheuk-Kwan; Ko, Ching-Chung; Fu, Pei-Han; Teng, I-Chia; Liu, Wei-Cheng; Lin, Chien-Ming; Hung, Kuo-Chuan (Frontiers in Medicine, 2022)
Background To evaluate the analgesic efficacy and risk of low-to-medium dose intrathecal morphine (ITM) (i.e., ≤0.5 mg) following cardiac surgery. Methods Medline, Cochrane Library, Google scholar and EMBASE databases were searched from inception to February 2022. The primary outcome was pain intensity at postoperative 24 h, while the secondary outcomes included intravenous morphine consumption (IMC), extubation time, hospital/intensive care unit (ICU) length of stay (LOS), and ITM-associated side effects (e.g., respiratory depression). Subgroup analysis was performed on ITM dosage (low: <0.3 mg vs. medium: 0.3–0.5 mg). Results Fifteen RCTs involving 683 patients published from 1988 to 2021 were included. Pooled results showed significantly lower postoperative 24-h pain scores [mean difference (MD) = −1.61, 95% confidence interval: −1.98 to −1.24, p < 0.00001; trial sequential analysis: sufficient evidence; certainty of evidence: moderate] in the ITM group compared to the controls. Similar positive findings were noted at 12 (MD = −2.1) and 48 h (MD = −1.88). Use of ITM was also associated with lower IMC at 24 and 48 h (MD: −13.69 and −14.57 mg, respectively; all p < 0.05) and early tracheal extubation (i.e., 48.08 min). No difference was noted in hospital/ICU LOS, and nausea/vomiting in both groups, but patients receiving ITM had higher risk of pruritus (relative risk = 2.88, p = 0.008). There was no subgroup difference in IMC except a lower pain score with 0.3–0.5 mg than <0.3 mg at postoperative 24 h. Respiratory depression events were not noted in the ITM group. Conclusion Our results validated the analgesic efficacy of low-to-medium dose ITM for patients receiving cardiac surgery without increasing the risk of respiratory depression.